UJI UNSUR HARA MAKRO PADA PUPUK KOTORAN MAGOT DARI HASIL BIOKONVERSI EKSKRETA AYAM: MACRO NUTRIENT TEST ON MAGOT MANURE FERTILIZER FROM CHICKEN EXCRETA BIOCONVERSION RESULTS - Maharani, Nadia; Susanti, Susanti (Universitas Boyolali, 2025)
This study aimed to examine the content of macronutrients (Nitrogen, Phosphorus, Potassium) and pH values in maggot manure fertilizer produced from the bioconversion of chicken excreta, and to compare it with commercial compost fertilizer available in the market. The research was conducted experimentally in the laboratory using two treatments: maggot manure fertilizer (P1) and commercial compost fertilizer (P2), with five replicates for each. Parameters analyzed included pH, nitrogen content (Kjeldahl method), phosphorus and potassium (wet ashing method), and total nutrient content, obtained by summing the N, P, and K levels. Data was analyzed descriptively and a significant difference was tested using an Independent Sample T-test. The results showed that pH values did not differ significantly between P1 and P2, indicating relatively similar soil pH stability from both types of fertilizer. However, maggot manure fertilizer (P1) had a significantly higher phosphorus content compared to commercial fertilizer (P2), demonstrating P1's great potential for root development and flowering. On the other hand, commercial compost fertilizer (P2) was significantly superior in nitrogen and potassium content, as well as overall total nutrient content, compared to P1. This aligns with the characteristics of chemical fertilizers, which are designed to deliver precise and high doses of macronutrients. Although the total nutrient content of P1 was lower, its 4.40% total nutrient content met the minimum requirement of Permentan No.1 Year 2019 (>2% NPK). In conclusion, commercial fertilizer excelled in the consistency and quantity of N and K, as well as total nutrients, while maggot manure fertilizer stood out in phosphorus content. The choice of fertilizer should be tailored to specific plant needs and soil conditions, making maggot manure fertilizer a potential good alternative or supplement, especially for increasing phosphorus availability by utilizing livestock waste.